Predictors of long term psychsocial outcome following traumatic brain injury. - Neil A Rutterford (2005)
Outcome after brain injury has, until recently, been assessed using few dimensions, and little attention has been paid to outcome at very late stages of recovery'. A broad range of variables have been found to be predictive of outcome after brain injury, but the nature of the relationship between predictors and outcome is unclear. This study aimed to include the majority of variables that have been reported as predictors, and used a model by Kendall and Terry (1996), based on a theory of stress and adjustment, as a framework to identify significant variables when predicting and explaining multidimensional long term outcome. 131 brain injured participants that were over 10 years post injury, were interviewed and neuropsychologically assessed. They also completed a set of questionnaires providing information about psychosocial variables. Results suggested that long term outcome can be good in this population, specifically in terms of quality of life and emotional adjustment. However, other outcomes, such as employment and community integration, were more severely compromised. Cognitive abilities showed no evidence of deterioration over time, but were still impaired in comparison to pre-injury estimates. Statistical analyses did not generally support the model depicting that appraisal and coping would act as mediators between predictors and outcome. Further analyses also rejected the notion that appraisal and coping were moderators. Predictors varied between dimensions, however, good self- concept, low neuroticism and high self-efficacy were found to be the most consistent significant variables when predicting all outcomes, and they also contributed the most to predictive models. When identifying predictors that directly influence outcome at late stages after brain injury, the findings indicated that the specific dimension of outcome being considered is all important. Furthermore, Kendall and Terry's model did not provide a useful framework to explain psychosocial adjustment.